The Transparency Level of Local Governments in Indonesia: Does the Level of Financial Health Matter? - Muhamad Rizal Yuniar; Amrie Firmansyah (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
This study examines the impact of fiscal autonomy, capital expenditure for basic services, and local government investment on the transparency level of local government. In addition, this study includes local government financial health as a moderator in the association between the dependent and independent variables. This study employs a quantitative approach. Data are obtained through content analysis of the local government's official websites. The total sample of this study amounted to 349 observations collected from 2016 to 2019 and was selected by purposive sampling. The hypothesis test employs multiple linear regression analysis with the ordinary least square. The study suggests that fiscal autonomy is positively associated with the transparency level of local governments, capital expenditure for basic services is negatively associated with the transparency level of local governments, and local government investment is not associated with the transparency level of local governments. This study also finds that local governments' financial health has a role in strengthening the positive effect of local government investment on the transparency level. However, the local government's financial health weakens fiscal autonomy's positive effect on the transparency level of local government. Furthermore, the local government's financial health has no moderator in the association between capital expenditure for basic services and the transparency level of local government. The study result suggests that the Indonesia Ministry of Finance and the Indonesia Ministry of Home Affairs should boost the policies that encourage transparency in local governments and enhance the independence level to generate local revenues.